Role Conflict and Role Ambiguity as Predictors of Job Stress Among Women Entrepreneurs: The Mediating Role of Work-Family Conflict - Syamsul Alam; Yana Fajriah; Nurhasni Muis; Muh Yushar Mustafa; Muh Al Fatah Arief Putra; Muh Irwan Nur Hamiddin (Journal of Economic Education and Entrepreneurship Studies, 2026)
Women entrepreneurs often face overlapping demands from business and family domains, making them particularly vulnerable to role-related stress. This study investigates the effects of role conflict and role ambiguity on job stress among women entrepreneurs in Makassar, Indonesia, with work-family conflict examined as a mediating mechanism. A quantitative explanatory design was employed, using data collected from 250 women entrepreneurs through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess both direct and indirect relationships among the constructs. The findings show that role conflict has a significant positive effect on job stress, whereas role ambiguity does not have a direct significant effect. However, both role conflict and role ambiguity significantly increase work-family conflict, which in turn exerts a significant positive effect on job stress. These results indicate that job stress among women entrepreneurs is shaped not only by work-related role pressures, but also by the spillover of incompatible demands across work and family domains. The study contributes to the women’s entrepreneurship literature by integrating role stress and work-family interface perspectives into a unified explanatory framework. Practically, the findings suggest that improving role clarity, minimizing incompatible role expectations, and strengthening boundary management strategies are essential for reducing job stress and sustaining women’s entrepreneurial engagement.